Patients with severe odontogenic infections receive insufficient dental treatment before hospitalization – a retrospective cross-sectional study - Rasmus Søndenbroe; Merete Markvart; Isabel Diaz-Pines Cort; Blaine Gabriel Fritz; Claus Henrik Nielsen; Thomas Bjarnsholt; Sanne Werner Møller Andersen; Simon Storgård Jensen (Acta Odontologica Scandinavica)
Objectives: The aim was to provide an in-depth characterization of patients hospitalized with severe odontogenic infections (SOI), especially in relation to the origin of the infection. Furthermore, the aim was to generate an overview of which kind of treatment the patients had received before hospitalization and to analyze risk factors for prolonged length of hospital stay.